The urban impacts of federal policies. Vol. 3, Fiscal conditions - Barro, Stephen M.; Rand Corporation; Charles F. Kettering Foundation; United States. Department of Health, Education, and Welfare (Santa Monica, CA : RAND, 1978)
This is the second of four reports examining the urban impacts of federal policies. It provides both a conceptual framework for policy impact analysis and a review of existing studies. The report examines the determinants of local fiscal conditions, the direct impact of federal policies on local fiscal outcomes, and also the indirect influence of federal policies that affect local households and businesses. A tentative agenda for future research is provided.
"April 1978."
Includes bibliographical references (p. 177-187) and index.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Cities and towns -- United States; Federal-city relations -- United States; Intergovernmental fiscal relations -- United States; Municipal finance -- United States